Reimagining Justice Delivery in India: Constitutional and Jurisprudential perspectives on Tribunalisation with Special Reference to the Food Safety Appellate Tribunal (International Journal of Food and Nutritional Sciences, 2022)
This article critically examines the constitutional and jurisprudential evolution of tribunalisation in India, situating it within the broader transformation of justice delivery mechanisms aimed at addressing judicial delay, procedural inefficiency, and increasing regulatory complexity. Drawing upon constitutional provisions, particularly Articles 14 and 21, and landmark judicial pronouncements, the study argues that tribunalisation represents a constitutionally mediated response to the crisis of access to justice rather than a mere administrative reform. The paper contextualises this development through empirical indicators, including the persistent judicial backlog—exceeding 4 crore pending cases across Indian courts—and structural constraints such as low judge-to-population ratios, which have necessitated alternative adjudicatory forums.Focusing specifically on the Food Safety Appellate Tribunal (FSAT) established under the Food Safety and Standards Act, 2006, the article evaluates its legal framework, institutional design, and functional performance. It analyses whether the FSAT successfully advances specialised, efficient, and accessible justice in food regulatory disputes while adhering to constitutional safeguards of fairness, independence, and judicial review. The study identifies critical challenges, including limited accessibility, inadequate institutional independence, fragmented jurisdiction, and lack of transparent jurisprudential development.By integrating doctrinal analysis with emerging empirical insights on tribunal performance, the article argues that while tribunalisation offers a viable pathway for reforming India’s justice delivery system, its effectiveness depends on robust institutional design, enhanced accountability, and alignment with rights-based constitutional principles. The paper concludes by proposing reforms to strengthen tribunal independence, improve accessibility, and integrate tribunal mechanisms within a holistic framework for realising substantive rights, particularly the right to safe and adequate food.